2011
DOI: 10.1182/blood.v118.21.795.795
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Symptoms in Myelofibrosis Patients Treated with Ruxolitinib Versus Best Available Therapy

Abstract: 795FN2 Background: Ruxolitinib (INC424), a potent and selective oral JAK1 and JAK2 inhibitor, demonstrated rapid and durable reductions in splenomegaly and improved disease-related symptoms, role functioning, and quality of life (QoL) in 2 phase 3 studies in patients with myelofibrosis (MF) (the COMFORT studies). Per-protocol, patient-reported, health-related QoL (HRQoL) and symptoms analyses in the COMFORT-II study are limited. Here we report on additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…suggestion of a survival advantage for patients receiving ruxolitinib, appropriately designed phase 3 studies, without the above-mentioned caveats, would be needed to demonstrate a survival benefit of this therapy. However, this does not undermine the efficacy of the drug in controlling 2 of the 3 main clinical manifestations of MF (namely, splenomegaly and constitutional symptoms), a fact that has a profound impact on the patient's quality of life, as it has been seen not only in clinical trials 32 but also in daily practice. In this sense, ruxolitinib can be considered the current BAT for the above 2 clinical manifestations of MF.…”
Section: Discussionmentioning
confidence: 99%
“…suggestion of a survival advantage for patients receiving ruxolitinib, appropriately designed phase 3 studies, without the above-mentioned caveats, would be needed to demonstrate a survival benefit of this therapy. However, this does not undermine the efficacy of the drug in controlling 2 of the 3 main clinical manifestations of MF (namely, splenomegaly and constitutional symptoms), a fact that has a profound impact on the patient's quality of life, as it has been seen not only in clinical trials 32 but also in daily practice. In this sense, ruxolitinib can be considered the current BAT for the above 2 clinical manifestations of MF.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were found by Harrison et al in an updated analysis of quality of life outcomes from COMFORT-II. 34 In this study, patients receiving ruxolitinib had persistently improved symptom status assessed by the QLC-C30 and global health status/ health-related quality of life as compared to patients receiving best available alternative therapy at weeks eight and 48. It has been hypothesized that the majority of these effects stem mainly from its anticytokine effects (eg, suppression of interleukin-6 and tumor necrosis factor-α) and, to a lesser extent, nonspecific immunosuppression.…”
Section: Symptom Burden Reliefmentioning
confidence: 71%
“…The importance of quality of life in this patient population is underscored by a post hoc analysis of the COMFORT-II study. 82 The analysis demonstrated that on average, health-related quality of life and MF symptoms improved in ruxolitinib-treated patients, whereas these measures remained the same or worsened in patients treated with best available therapy. In a separate analysis, severe disease-related symptoms were found to be associated with a diminished health-related quality of life.…”
Section: Comfort-ii Ismentioning
confidence: 97%